Introgression between Betula tianshanica and Betula microphylla and its implications for conservation. Issue 4 (3rd February 2021) - Ding, Junyi; Hua, Donglai; Borrell, James S.; Buggs, Richard J. A.; Wang, Luwei; Wang, Feifei; Li, Zheng; Wang, Nian
Societal Impact Statement: In rapidly changing environments species conservation can be hindered by uncertainties in distinguishing closely related species. Cryptic ongoing hybridization can add further uncertainty and could be beneficial or destructive. Here, we show that a declining birch tree species is hybridizing with a more widespread relative in the Junggar basin, NW China, and their hybrids have been previously named as rare sub‐species. Given the declining numbers of this birch tree, we suggest that conservation effort should aim to slow the rate of anthropogenic habitat loss at this hybrid zone and preserve its pure populations away from the hybrid zone. Summary: In areas where closely related species meet, the possibility that they may hybridize must be taken into account by conservationists. Hybridization may have positive or negative consequences for the long‐term future of species. If present, its dynamics need to be understood. Betula microphylla is a declining wetland tree species in NW China that forms a continuum of leaf morphology and geographic distribution with its relative Betula tianshanica . We use ecological niche models to predict the distribution of B. microphylla and B. tianshanica . We use restriction site‐associated DNA sequencing and SSRs to resolve their genetic structure and patterns of allele sharing. Ecological niche models predict an expansion of the range of B. tianshanica into that of B. microphylla since the Last Glacial Maximum and the contraction of B. microphylla's range in the future. Genetic data suggest that the two species have hybridized in the Junggar basin and in the Tianshan Mountains where the two species have co‐occurred in the recent past and in the Altay Mountains where there are no records of B. tianshanica occurrence. Rare populations previously identified as sub‐species of B. microphylla were shown to be of hybrid origin. Further research is needed on the costs and benefits of hybridization between B. microphylla and B. tianshanica in the changing environment of NW China. Our current data suggest that conservation effort should aim to slow the rate of anthropogenic habitat loss at the hybrid zone in the Junggar basin and preserve pure populations far away from the hybrid zone in the Altay Mountains. Abstract : In rapidly changing environments species conservation can be hindered by uncertainties in distinguishing closely related species. Cryptic ongoing hybridization can add further uncertainty and could be beneficial or destructive. Here, we show that a declining birch tree species is hybridizing with a more widespread relative in the Junggar basin, NW China, and their hybrids have been previously named as rare sub‐species. Given the declining numbers of this birch tree, we suggest that conservation effort should aim to slow the rate of anthropogenic habitat loss at this hybrid zone and preserve its pure populations away from the hybrid zone.